Correction: Effect of surfactant on Pseudomonas aeruginosa colonization of polymer microparticles and flat films. Issue 34 (24th May 2018) - Hüsler, Amanda; Haas, Simon; Parry, Luke; Romero, Manuel; Nisisako, Takasi; Williams, Paul; Wildman, Ricky D.; Alexander, Morgan R.
Abstract : Correction for 'Effect of surfactant on Pseudomonas aeruginosa colonization of polymer microparticles and flat films' by Amanda Hüsler et al., RSC Adv., 2018, 8, 15352–15357.